Bioactive compounds content and their biological properties of acetone extract of Cuscuta reflexa Roxb. grown on various host plants - K. Tanruean (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group The present study is aimed to evaluate the total phenolic and flavonoid contents, and free phenolic compounds of acetone extract of Cuscuta reflexa grown on five different hosts: Coccinia grandis, Ficus racemosa, Samanea saman, Streblus asper and Zollingeria dongnaiensis, and to explore the antioxidant activities, α-glucosidase and tyrosinase inhibitory properties of the extracts. The highest level of total phenolic and flavonoid contents were observed in the extract of C. reflexa that was grown on S. asper (65.45 mg GAE/g extract) and C. grandis (97.83 mg QE/g extract), respectively. According to HPLC results, vanillic acid, rutin and quercetin were found in all extracts of C. reflexa grown on diversified hosts. The extract of C. reflexa grown on C. grandis possessed the greatest antioxidant activities (DPPH; 251.64 μg/mL, FRAP; 26.44 mg GAE/g extract), α-glucosidase inhibition accounted for 84.36 per cent and antityrosinase activity was at 18.29 mg KAE/g sample.